Hubungan Terapi Relaksasi Otot Progresif dengan Tekanan Darah pada Lansia yang Menderita Hipertensi - Mandaty, Fhandy Aldy; Syaifudin, Achmad; Sumarno, Sumarno (STIKes Persada Husada Indonesia, 2024)
Hypertension has become the most common health problem suffered by the elderly. Hypertension that is not controlled and occurs for a long time can cause various other serious health problems and even death. Progressive muscle relaxation is a non-pharmacological way to reduce hypertension in the elderly. The aim of this study was to analyze the relationship between progressive muscle relaxation therapy and blood pressure in hypertensive elderly people. This type of research is quasi experimental design with pre test and post test without control. The sampling technique used is total sampling. The research sample consisted of 36 hypertensive elderly. The results of the research were a decrease in blood pressure in 36 research respondents, both systolic and diastolic, after giving progressive muscle relaxation. The results of statistical tests on the systolic and diastolic blood pressure variables also show that the p value is 0.000, meaning that there is a significant relationship between giving progressive muscle relaxation therapy and blood pressure in hypertensive elderly people. Conclusion: The results of this study indicate that there is a significant relationship between progressive muscle relaxation therapy and blood pressure in elderly people suffering from hypertension. Progressive muscle relaxation can be used as an alternative therapy for hypertensive elderly people.